5-4x-13=3

Simple and best practice solution for 5-4x-13=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-4x-13=3 equation:


Simplifying
5 + -4x + -13 = 3

Reorder the terms:
5 + -13 + -4x = 3

Combine like terms: 5 + -13 = -8
-8 + -4x = 3

Solving
-8 + -4x = 3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + 8 + -4x = 3 + 8

Combine like terms: -8 + 8 = 0
0 + -4x = 3 + 8
-4x = 3 + 8

Combine like terms: 3 + 8 = 11
-4x = 11

Divide each side by '-4'.
x = -2.75

Simplifying
x = -2.75

See similar equations:

| -1.5X=-6.25 | | (3/8)/(3/4)=x | | 16-5m-4m-2+2m= | | 3/8/3/4=x | | x/-5+29=12 | | (2+2x+9x^2+4x^3)-(-1+2x-9x^2+4x^3)= | | 4x+45=144 | | 2(10)-y=19 | | g+(g+8)+(g+8)+(g+8)+(g+8)=200 | | 3(x+8)-11x=-8(x+4)-11 | | -21+2x=24-3x | | x-9=6x+9 | | 1=7x+8 | | 1=s-23 | | 20(x-80)=40 | | -16=-18x | | 4p^2-60p+400=0 | | -4y+10=4+9y | | -2(t-2)+4t=5t-3 | | 59=9x-4 | | 40=10-5x | | X+(3x-4)(-2)=10 | | -5(t-4)+9t=8t-6 | | 400=4p(18-(3+p)) | | (2x-1)(x-4)+(x-5)(x-5)-(x-4)(3x-4)=-11 | | y+3=-1/4 | | x^2+3600=150x | | 0=4x-9 | | 20-(-4)+1= | | -4t+16+8t=7t-4 | | 18-m=75 | | x+34=26 |

Equations solver categories